2018
DOI: 10.1155/2018/1398958
|View full text |Cite
|
Sign up to set email alerts
|

An Engagement Model Based on User Interest and QoS in Video Streaming Systems

Abstract: With the surging demand on high-quality mobile video services and the unabated development of new network technology, including fog computing, there is a need for a generalized quality of user experience (QoE) model that could provide insight for various network optimization designs. A good QoE, especially when measured as engagement, is an important optimization goal for investors and advertisers. Therefore, many works have focused on understanding how the factors, especially quality of service (QoS) factors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…One novelty in this paper can be easily identified in the special case of initial buffering, which was tested in experiments D and E and is marked in Figure 5 by lines segment. It can be seen that user drop increases non-linearly with the initial buffering duration (as expected from past studies [26], [28]), but large differences between experiments D and E are found. Indeed, in experiment E, users reacted more sharply to initial buffering than in experiment D due to the differences in total stalling duration between experiments D and E (272 and 341 s, respectively).…”
Section: Quitting Ratio and Stalling Eventssupporting
confidence: 85%
See 2 more Smart Citations
“…One novelty in this paper can be easily identified in the special case of initial buffering, which was tested in experiments D and E and is marked in Figure 5 by lines segment. It can be seen that user drop increases non-linearly with the initial buffering duration (as expected from past studies [26], [28]), but large differences between experiments D and E are found. Indeed, in experiment E, users reacted more sharply to initial buffering than in experiment D due to the differences in total stalling duration between experiments D and E (272 and 341 s, respectively).…”
Section: Quitting Ratio and Stalling Eventssupporting
confidence: 85%
“…Second, stalling midway through a video is discussed. In this case, abandonment is found to increase logarithmically with the stalling duration [26], [28]. Going from 12 to 24 s results in abandonment increasing by 30% [29].…”
Section: Related Workmentioning
confidence: 75%
See 1 more Smart Citation
“…Then, another significant body of work worth mentioning is the studies of the relationship between viewing time and quality impairments such as initial loading delay [40]- [42] and midway-though stalling [43], [44]. These studies showed that the odds of users quitting increase exponentially as they need to wait for the video to play.…”
Section: Towards Measuring Engagementmentioning
confidence: 99%
“…In [41], [42] the authors considered user engagement as their target QoE metric. In particular, in [42] the authors accounted for users' interests and QoS factors to build an engagement/QoE predictive model. Our approach is aligned with this integrated perspective to predict QoE.…”
Section: A Qos and Qoe Parametersmentioning
confidence: 99%